2014
DOI: 10.1016/j.vaccine.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein B (gB) vaccines adjuvanted with AS01 or AS02 protect female guinea pigs against cytomegalovirus (CMV) viremia and offspring mortality in a CMV-challenge model

Abstract: The transmission of cytomegalovirus (CMV) from mother to fetus can give rise to severe neurodevelopment defects in newborns. One strategy to prevent these congenital defects is prophylactic vaccination in young women. A candidate vaccine antigen is glycoprotein B (gB). This antigen is abundant on the virion surface and is a major target of neutralization responses in human infections. Here, we have evaluated in a challenge model of congenital guinea pig CMV (GPCMV) infection, GPCMV-gB vaccines formulated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
5
32
0
Order By: Relevance
“…The protection conferred following immunization with the ⌬145 vaccine was comparable to that conferred by natural GPCMV seropositivity (23) or by preconception vaccination with adjuvanted, purified recombinant gB (22,37), on the basis of comparisons of our results with those of other studies. Mortality data were previously evaluated in a study in pups born to naturally GPCMV-seropositive dams challenged with SG-passaged virus, using the same experimental design used in this study (23).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The protection conferred following immunization with the ⌬145 vaccine was comparable to that conferred by natural GPCMV seropositivity (23) or by preconception vaccination with adjuvanted, purified recombinant gB (22,37), on the basis of comparisons of our results with those of other studies. Mortality data were previously evaluated in a study in pups born to naturally GPCMV-seropositive dams challenged with SG-passaged virus, using the same experimental design used in this study (23).…”
Section: Discussionsupporting
confidence: 68%
“…In that study, five pregnant dams were challenged with the same dose of SG-passaged virus used in this study, and pup mortality was 29% (4/14), which is statistically significantly comparable to the mortality rates that we observed in ⌬145-immunized dams. In studies from the CIDMTR laboratory of purified, recombinant gB vaccine adjuvanted with Freund's adjuvant, pup mortality rates have ranged from 14 to 36% and vertical transmission rates have ranged from 22 to 73% (22,37). Thus, the metrics of protection conferred by the ⌬145 vaccine compare very favorably to those associated with natural seropositivity or adjuvanted protein subunit immunization reported previously.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The study of guinea pig cytomegalovirus (GPCMV) is particularly valuable, since this virus will cross the placenta and infect pups in utero, leading to congenital transmission (5). Thus, the GPCMV model has been utilized to examine a variety of subunit vaccine and antiviral therapy strategies relevant to human health (6)(7)(8).Prior studies reported the successful cloning of the genome of a tissue culture-attenuated variant of GPCMV strain 22122 as a bacterial artificial chromosome (BAC) designated N13R10 (9). Although virus derived from N13R10 grows like wild-type GPCMV in cell culture, it was highly attenuated in vivo compared to pathogenic salivary gland (SG)-adapted virus.…”
mentioning
confidence: 99%